Problematizando experiências de vítimas de violência : indagações e análises - Mansur, Thiago Sandrini (2009)
In general, reflections over people that suffer some kind of violence have been neglected for a long time by societies all over the world. This became more emphasized within less favored portions of the society. This scenario has been slowly modifying itself in Brazil throughout the 20th century, added by new experiences provided by human rights movements, starting from the end of military dictatorship era. In a more recent timeframe in our history, the creation of violence victim s support centers could be considered as a way to study the many forms of violence, however those centers are not the only ones and not the first to do it. Those centers have become a place not only for victims of violence attendance, but also to start a discution for a non-violent and peaceful culture. With that scenario set up, the objective was to focus on violence victims on the Grande Vitória area. That means ask yourself how some practices mostly accepted without questioning, as a regular and common or cultural practice become real preoccupations, raising debates and behavior change. Some group activities were experienced with mothers which sons have been exposed to State agents, during social-educational correction time. There were also feedback interviews with those mothers, who could evaluate the group experience, as well as discuss the research s effectiveness and results. This research resulted in life affirmation, although people continue to suffer the effects of violence instead of not fighting back. It was felt that knowing and sharing the experiences of these people can contribute to the academic discussion of the problem and the transformation of some of the deleterious effects of violence